Aeroelastic Analysis of a Typical Section Using of Shape memory wire actuator - Piccirillio, Vinicius; Goes, Luiz Carlos Sandroval; Balthazar, José Manoel [UNESP] (My University, 2011)
Shape memory alloys (SMAs) provide a compact and effective actuation for a variety of mechanical systems. In this paper, a numerical simulation study of a three degree of-freedom airfoil, subjected to two-dimensional incompressible inviscid flow using a SMA is presented. SMA wire actuators are used to control the flap movement of a wing section. Through the thermo-mechanical constitutive equation of the SMA proposed by Brison, we simulate numerically the behavior of a double SMA wire actuator. Two SMA actuators are used: one to move the flap down and the other to move the flap up. Through the numerical results conducted in the present study, the behavior and characteristics of an SMA actuator with two SMA wires are shown the effectiveness of the SMA actuator. In conclusion, this paper shows the feasibility of using SMA wire actuators for flap movement, with success
Keywords: Shape memory alloys; SMA wire actuator; Nonlinear Dynamics and Control